Metastasiertes kastrationsresistentes Prostatakarzinom = Metastatic castration-resistant prostate cancer : clinical data, new treatment options and therapy monitoring - Miller, Kurt; Mickisch, Gerald (Der Urologe, 2016)
Therapies currently available in Germany for metastatic castration-resistant prostate cancer (mCRPC) include docetaxel, cabazitaxel, abiraterone acetate, enzalutamide and radium-223, all of which offer a potential survival benefit that adds up in their sequential application to a significant overall survival benefit. However, the optimal sequencing of these agents is still unclear. In the absence of evidence, treatment selection is based on the particular situation and on comorbid conditions of each individual patient. Furthermore, predictive markers to facilitate the selection of patients for a specific therapy or sequence of therapies remain an unmet need. However, with the recently discovered androgen receptor splice variant V7, which mediates (cross)resistance to or between abiraterone and enzalutamide, the first such marker has been identified. It is critical to monitor the response to treatments at prespecified intervals in order to optimize treatment sequencing so that the patient does not miss a valuable therapeutic window to receive alternative treatment that may prolong his life along with good symptom control and preservation of quality of life.
Gesehen am 12.12.2019